Analysis of Determinant Factors on Patient Satisfaction in the Emergency Department - Rima Faradila; Indasah Indasah; Nurwijayanti Nurwijayanti; Farida Farida (Indonesian Journal of Global Health Research, 2026)
Patient satisfaction is a crucial indicator of healthcare quality, particularly in the Emergency Department (ED), where services must be rapid, accurate, and compassionate. This study aimed to analyze determinant factors influencing patient satisfaction in the Emergency Department of Bhayangkara Hospital Tulungagung. A quantitative cross-sectional design was applied to 110 ED patients selected through systematic random sampling. Data were collected from November 24–30, 2025, using a SERVQUAL-based questionnaire measuring responsiveness, assurance, tangibles, empathy, reliability, and response time. Instrument testing showed that all items were valid (r count > 0.413) and reliable (Cronbach’s Alpha > 0.70). Data analysis using Spearman’s rho correlation and logistic regression revealed that all service quality dimensions were positively and significantly associated with patient satisfaction (p < 0.05). Responsiveness had the strongest correlation (r = 0.748), followed by empathy (r = 0.710). Logistic regression identified empathy as the most dominant determinant (β = 0.458). These findings indicate that empathetic care and interpersonal interactions play a central role in improving patient satisfaction in the ED.